2004
DOI: 10.1136/jmg.2004.022111
|View full text |Cite
|
Sign up to set email alerts
|

Sequence family variant loss from the AZFc interval of the human Y chromosome, but not gene copy loss, is strongly associated with male infertility

Abstract: Background: Complete deletion of the complete AZFc interval of the Y chromosome is the most common known genetic cause of human male infertility. Two partial AZFc deletions (gr/gr and b1/b3) that remove some copies of all AZFc genes have recently been identified in infertile and fertile populations, and an association study indicates that the resulting gene dose reduction represents a risk factor for spermatogenic failure. Methods: To determine the incidence of various partial AZFc deletions and their effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
185
4
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(207 citation statements)
references
References 30 publications
(51 reference statements)
13
185
4
5
Order By: Relevance
“…Some studies suggested a link between a partial deletion in the AZFc region and spermatogenic failure [35,36]. However other studies have disagreed, proposing it to be simply a polymorphic deletion with no clinical ramification [37].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggested a link between a partial deletion in the AZFc region and spermatogenic failure [35,36]. However other studies have disagreed, proposing it to be simply a polymorphic deletion with no clinical ramification [37].…”
Section: Discussionmentioning
confidence: 99%
“…Deletions of DAZ and CDY1 gene copies were analysed using sequence family variant (SFV) analysis [41,42]. Briefly for DAZ gene copy deletions, sY581 and sY587 were amplified and digested overnight using Sau3AI and DraI restriction enzyme (Thermo Fisher Scientific Inc., Waltham, Massachusetts, USA), respectively.…”
Section: Detection Of Daz and Cdy1 Gene Copy Deletionsmentioning
confidence: 99%
“…Fourteen controls were selected according to their molecular and cytogenetic characteristics : -DNA from a patient with a complete AZFb deletion (P5 -proximal P1; AZFb -del) as a partial deletion control (lack of DAZ1-DAZ2 cluster) [4,16] -DNA from a man carrying a t(X;Y)(qter->p22::q11->qter) as a duplication control [19] -DNA from a 47,XYY male was also included to valid the Q-PCR technique -DNA from 8 patients previously studied and characterized with FISH and quantitative techniques: 2 "b2-b3" partial deletion, 1 "gr-gr" partial deletion, 2 deletions followed by duplication and 3 with no AZFc rearrangements [11]. DNA from a man with proven fertility was chosen as a positive control and as a reference for Q-PCR, and female DNA as well as DNA from a man with an AZFc microdeletion (AZFc-del) were used as a negative control.…”
Section: Patientsmentioning
confidence: 99%
“…Contrary to "complete" AZF deletions, the clinical relevance of partial deletion is still discussed. Indeed, several studies have shown the existence of partial AZFc deletions responsible for the loss of one cluster of the DAZ genes in fertile men [10][11][12]. In addition to deletion, duplication events and deletion followed by duplication events were identified, but their consequence in male infertility are unknown [3,5,11,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation